Introduction: Latin America in the global time - Rojas Castro, Daniel Emilio (Ciencia Nueva, revista de Historia y Política, 2019)
Thinking of Latin America as a starting point to understand the articulation of the world in the same spatial and temporal unit is a project so vast and ambitious, that it is enough to discourage the most obstinate of researchers. Although it seems a more fabulous task than possible, closer to the twelve works of Hercules than to the modest possibilities of professional historians, the need to understand the emergence and expansion of a global time that does not privilege a perspective centered on North Atlantic societies is today more relevant than ever. The world is not the same for everyone. Building a global perspective of Latin American history has a double purpose: on the one hand, it is an invitation to think about the historical experience of the subcontinent through connections, exchanges and circulations between this space and the rest of the world. On the other, it is a methodological challenge for Global history, a new disciplinary field that, despite its global vocation, has created epistemological peripheries and reproduced geopolitics of knowledge that only partially includes large areas of the world such as Latin America and Africa.